2007
DOI: 10.1002/hrdq.1219
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating storytelling into practice: How HRD practitioners foster strategic storytelling

Abstract: HRD practitioners are adding storytelling to their box of tactical and strategic tools. This qualitative research study investigates how HRD practitioners in forprofit settings apply storytelling as a means of advancing organizational goals. The primary focus of practitioners is on instrumental application of stories through face-to-face performance, and the decisions they make regarding the "mechanics" of the process: getting storytelling started, finding and selecting stories, and identifying or creating ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
0
20
0
3
Order By: Relevance
“…In doing so, we reveal the dynamic and somewhat uneasy interplay between the different sorts of narratives that are woven through the CEO's innovative liberation management project. Finally, these findings are discussed in terms of the reviewed literature to show how they provide evidence that not only do narratives operate as tactical and strategic tools (Tyler, 2007), they also construct power relations (Boje & Smith, 2010), advance organizational goals (Tyler, 2007) and at the same time challenge this advance by virtue of the cacophony of narratives created. While we accept Vaara's (2010) proposal that there are multiple levels (i.e., micro, meso, and macro) of organizational discourse, our analysis has been restricted to the often-overlooked meso level where narratives are in the making.…”
Section: Liberation Through Narrativity: a Case Of Organization Reconmentioning
confidence: 95%
See 1 more Smart Citation
“…In doing so, we reveal the dynamic and somewhat uneasy interplay between the different sorts of narratives that are woven through the CEO's innovative liberation management project. Finally, these findings are discussed in terms of the reviewed literature to show how they provide evidence that not only do narratives operate as tactical and strategic tools (Tyler, 2007), they also construct power relations (Boje & Smith, 2010), advance organizational goals (Tyler, 2007) and at the same time challenge this advance by virtue of the cacophony of narratives created. While we accept Vaara's (2010) proposal that there are multiple levels (i.e., micro, meso, and macro) of organizational discourse, our analysis has been restricted to the often-overlooked meso level where narratives are in the making.…”
Section: Liberation Through Narrativity: a Case Of Organization Reconmentioning
confidence: 95%
“…Indeed, recent literature establishes narratives and storytelling as tactical and strategic tools (Boje, 2008;Vaara & Reff Pedersen, 2013). According to Tyler (2007), narratives advance organizational goals through the way they are embodied in all manner of official actions and associated texts including those operating at the meso organizational level (e.g., in general meetings, organizational chart, principles, rules, procedures, technologies, and websites) (Boje & Smith, 2010). At the micro level, narratives engage with the rhetorical activity at the center of organizational strategizing (Jarzabkowski & Seidl, 2008) and more informal encounters such as everyday discussions (Samra-Fredericks, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In their article on using organizational storytelling as a crisis management tool, Kopp et al (2011) review and discuss a wide variety of ways in which stories are used in organizations, including: to describe workplace experiences, as a vehicle to espouse key values, to support change, to inspire action and to enable sensemaking. Tyler (2007) explored how Human Resource Development (HRD) practitioners foster 'strategic storytelling' and has suggested a very comprehensive framework that maps the key connections that place storytelling squarely within the discipline of HRD. In some of these approaches, individuals are encouraged to tell their own stories; in others, stories are located and chosen to be explicitly used by key organizational participants (leaders, HRD practitioners, etc.…”
Section: A Theoretical Frameworkmentioning
confidence: 99%
“…Storytelling has also been highlighted in the adult learning literature by Bandura (1977) and Weick (2000) in that stories can serve as models of excellence. These models allow adults to see themselves in a narrative and mentally rehearse or visualize themselves performing the behavior highlighted in the story (Tyler, 2007). The management research has found narrative to have a role in developing organizational culture (Brady & Haley, 2013, Dailey & Browning, 2014Parada & Viladas, 2010), strategic management (Sonenshein, 2010), employee loyalty (Gill, 2011), organizational commitment (McCarthy, 2008), and entrepreneurship (Volker, Phillips, & Anderson, 2011).…”
Section: Introductionmentioning
confidence: 99%